2018
DOI: 10.13005/ojc/340639
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Method for Determination of Nitrite and Nitrate Levels in Broccoli and Cauliflower with Different Fertilization Treatment

Abstract: Both broccoli and cauliflower are plants that are widely cultivated and consumed. The vegetable also contains Nitrite and Nitrite, which have a negative impact on human health because of the carcinogenic effect. Levels of Nitrite and Nitrate in vegetable are dependent on several factors, one of them is fertilization. The objective of this research is to determine the levels of Nitrite and Nitrate in broccoli and cauliflower without fertilization and with fertilization (natural and chemical). Samples were plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This result suggests that it is possible to substitute totally or partially mineral fertilizers with organic ones, thus promoting the sustainability of organic production, as found in a different environment with other organic materials on the same crop [47]. The nitrate levels in the cauliflower samples in our study are in line with those previously reported for the Chambord F1 cauliflower cultivar [48] and for cauliflower seedlings [49], showing no effect of the six different fertilization strategies applied on the preferential accumulation of these compounds. Given that cauliflower grows well at 18-25 • and, consequently, takes advantage of days with good sunlight, it is presumable that the low concentration of nitrates found in the cauliflowers coming from the six different fertilization strategies may be attributable, in addition to the cultivation techniques, also to the position and exposure of the field, which favored good radiation and helped the reduction of nitrates.…”
Section: Total and Inorganic Nitrogensupporting
confidence: 91%
“…This result suggests that it is possible to substitute totally or partially mineral fertilizers with organic ones, thus promoting the sustainability of organic production, as found in a different environment with other organic materials on the same crop [47]. The nitrate levels in the cauliflower samples in our study are in line with those previously reported for the Chambord F1 cauliflower cultivar [48] and for cauliflower seedlings [49], showing no effect of the six different fertilization strategies applied on the preferential accumulation of these compounds. Given that cauliflower grows well at 18-25 • and, consequently, takes advantage of days with good sunlight, it is presumable that the low concentration of nitrates found in the cauliflowers coming from the six different fertilization strategies may be attributable, in addition to the cultivation techniques, also to the position and exposure of the field, which favored good radiation and helped the reduction of nitrates.…”
Section: Total and Inorganic Nitrogensupporting
confidence: 91%
“…Studies have been shown that NO3 content of plants edible parts were influenced by fertilization amount and type (Liu et al, 2014). Nerdy et al, (2018) reported that NO3 content of cauliflower elevated with increasing nitrogen ratio that incorporated into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate reductase (NR) and nitrite (NIR) activity was measured as suggested by Srivastava (1975) and Losada and Paneque (1971) based on the nitrate reduction at 540 nm. Total nitrite and nitrate-N content were estimated by acid digestion (Nerdy and Putra, 2018). The superscript defines the significant differences among the treatments.…”
Section: Nitrate Reductase Activity and Nitrite Nitrate Estimationmentioning
confidence: 99%